On the perception of the law on the example of an agricultural case referred to in the Act on shaping the agricultural system - Truszkiewicz, Zygmunt (Przegląd Prawa Rolnego, 2023)
The article illustrates the relationship between the perception of the law and its practical application. For this purpose, a case was used in which controversies arose concerning the application of the Act on shaping the agricultural system. Those controversies boiled down to the question of whether the regulations contained in this Act and concerning the acquisition of agricultural real estate should also apply in the case of the transformation of a limited liability company into a limited partnership. The deliberations performed showed that the legal assessment of the same issue may differ depending on whether the person making the assessment adheres to a positivist or natural law perception. The former tends to lead the interpreter to rely mainly on a literal interpretation, while the latter tends to rely on other methods of interpretation, including a functional-objective interpretation. The latter even implies the need to verify positive law and to concretise legal norms in atypical cases. Such an approach allows to avoid legal assessments that lead to consequences that are, on the one hand, in line with the literal reading of the rules and, on the other hand, irrational and therefore unjust and wrong.